Overcoming the sorafenib resistance mechanism in FLT3-mutated acute myeloid leukemia: molecular basis and new targets - Peng, Hui; Li, Min; Peng, Yuan Yuan; Li, Xiao Lan; Yang, Jing; Sun, Qiang Ge; Song, Kui (Frontiers in Oncology, 2025)
Acute myeloid leukemia (AML) originates from myeloid hematopoietic stem cells. Approximately 30% of patients exhibit FMS-like tyrosine kinase 3 (FLT3) mutations clinically, which is associated with a poor prognosis. FLT3 tyrosine kinase inhibitors (FLT3-TKIs), including sorafenib, demonstrate efficacy in FLT3-mutated AML, but resistance remains a significant challenge. However, various mechanisms have led to the rapid development of resistance to sorafenib treatment, including both primary and secondary drug resistance. Primary resistance refers to sorafenib’s initial treatment failure due to redundant signaling pathways and tumor heterogeneity, while secondary resistance develops after prolonged therapy through new genetic mutations or activation of alternative pathways. This study systematically examines mechanisms of sorafenib resistance in AML, including tumor genetic changes and the bone marrow microenvironment. It outlines classic mechanisms, such as FLT3 functions, kinase mutations, and cellular signaling pathways, while also addressing gaps in knowledge regarding resistance driven by metabolic factors and the bone marrow environment. Furthermore, the paper explores novel FLT3 inhibitors and combination therapies, while outlining future directions for precision intervention through dynamic monitoring of clonal evolution. This review provides a comprehensive framework for understanding and addressing sorafenib resistance, offering insights into future therapeutic strategies for FLT3-mutated AML.